Is There A Way to Prevent Aging? A Study Using Metformin in Blood Sugar Levels and Serum Levels of IGF-1 - Arlina Wiyata Gama; Arief Santoso; Ika Yustisia; Nurpudji Astuti Taslim; Irfan Idris; Isra Wahid (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2021)
Aging is influenced by lifestyle, which one is by consuming excessive calories. In recent years there have been many studies on aging and age-related diseases, calorie restriction mimetic is one of them. Metformin is a calorie restriction mimetic that is attractive to gerontologists. This research analyzed the effect of metformin as a calorie restriction mimetic on fasting blood glucose and IGF-1 serum levels in old white male Wistar rats. This study conducted with an experimental study with a pre and post-test pattern with controlled group design on male rats (Rattus novergicus) Wistar strain which was divided into 3 groups, control group (K), the calorie restriction group (P1), and the metformin group (P2), 6 rats each group. Blood glucose levels were measured by a glucometer and serum IGF-1 levels were measured with an ELISA kit, where blood samples were taken from the tail of the rats. In general, the provision of metformin and calorie restriction tended to reduce blood glucose levels, but increased serum IGF-1 levels. There is a significant relationship between blood glucose levels and serum IGF-1 levels. It’s necessary to conduct further research to determine the effective dose and maximum dose of metformin to reduce blood glucose level and serum IG-1 levels which can be slow down the aging process.